Inovasi Teknologi Peradilan Modern (E-Court) Mahkamah Agung Republik Indonesia dalam Menjawab Tantangan Global - Indra Budi Jaya; Ivan Tanoto; Muhammad Ainun Luthfi; Afifah Nur Hamidah; Amalia Mar’ah Sholihah; Indah Sari Fadillah; Muhammad Fauzan Irsyad; Alya Frianka; Heni Halimatussyadiah; M. Maula Yasar; Seni Agustiani; Farid Dwi Andrian; Firda Salsabila Nuratu (FKIP, Universitas Palangka Raya, 2024)
Technological innovation in the modern judicial system has become a primary focus of the Supreme Court of the Republic of Indonesia in addressing global challenges. The Supreme Court of the Republic of Indonesia has introduced the latest innovations in judicial technology to enhance the efficiency, accessibility, and fairness of judicial procedures, known as electronic courtroom or e-judiciary. The purpose of this research is to analyze the implementation of the latest innovations related to judicial technology (electronic judiciary) in the Supreme Court of the Republic of Indonesia in order to address global challenges to the judicial system. The researcher examines the technology used in the electronic courtroom, its benefits, the challenges it poses, and its impact on the effectiveness and transparency of the judicial system. Through an in-depth review of the implementation of e-courtrooms in the Supreme Court of the Republic of Indonesia, we present findings on the success of this innovation in addressing the global challenges faced by the judicial system.